Korean "comfort women": military brothels, brutality, and the redress movement - Min, Pyong Gap (Genocide, political violence, human rights series, 2021)
Introduction : background information about Japanese military sexual slavery and the redress movement for the victims -- Theoretical and conceptual frameworks -- Enough information, but the issue buried for half century -- The emergence of the "comfort women" issue and victims' breaking silence -- General information about the comfort women system -- Forced mobilization of comfort women -- Payments of fees and affectionate relationships -- Sexual exploitation, violence, and threats at "comfort stations" -- Perils of Korean "comfort women's" homecoming trips -- Korean "comfort women's" life in Korea and China -- Progress of the redress movement in Korea -- Divided responses to the redress movement in Japan -- Responses to the redress movement in the United States --Conclusion.